2018
DOI: 10.1007/s10068-018-0389-y
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of lipid and protein extractions from Spirulina platensis using ultrasound assisted osmotic shock method

Abstract: In this study, we optimized the process for extracting lipids and proteins from wet biomasses of Spirulina sp. using a 4-kHz ultrasonic osmotic shock method with ultrasound enhancement at a constant frequency of 40 kHz. Optimization was conducted using a response surface methodology (RSM) at an osmotic NaCl concentration of 10-30%, solvent:biomass ratio of 5-15 v/ w, and extraction times of 20-50 min. The present osmotic shock method with ultrasound irradiation increased lipid yields to 6.65% in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Linoleic and gamma-linolenic acids were found as the most abundant PUFAs. The content of gamma-linolenic acid (13.4%) was almost similar to that reported for Spirulina platensis (15.2%) [ 29 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Linoleic and gamma-linolenic acids were found as the most abundant PUFAs. The content of gamma-linolenic acid (13.4%) was almost similar to that reported for Spirulina platensis (15.2%) [ 29 ].…”
Section: Resultssupporting
confidence: 82%
“…Process parameters, such as an osmotic NaCl concentration of 10–30%, solvent: biomass ratio of 5–15 v / w , and extraction times of 20–50 min, were investigated for the extraction of lipids from Spirulina platensis using a response surface methodology. The findings suggested that the applied osmotic shock method with ultrasound irradiation increased lipid yields to 6.65% using 11.9% NaCl, a solvent: biomass ratio of 12:1 v / w , and an extraction time of 22 min [ 29 ]. In addition, lipid yields ranging from 6.4 to 7.5% (DW) were reported for Spirulina platensis , Spirulina maxima , and Spirulina spp.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of different FeSO 4 concentrations (0, 0.005, 0.01, 0.05, and 0.1 g/L) on the content of the individual fatty acids is recorded in Table 1 which describes the influence of different ferrous sulfate values on palmitic acid, oleic acid, linoleic acid, gamma-linolenic acid, and docosahexaenoic acid in Arthrospira platensis. According to the literature, the selected five fatty acids are the most abundant in A. platensis [76,77]. The chromatograms of gas chromatography (GC) for palmitic acid, oleic acid, linoleic acid, γ-linolenic acid, and docosahexaenoic acid in A. platensis revealed that spirulina at higher iron concentrations has a major percent of fatty acids.…”
Section: The Effect Of Feso 4 Concentrations On the Fatty Acid Profilementioning
confidence: 99%
“…It is indicated by its protein content has high range from 46-63% [4]. In addition, it is also enriched by various essential acids including histidine, threonine, methionine, valine, lysine, cysteine, and other non-essential amino acids [5]. This has drawn huge attention for researchers to study the application of the protein from Spp into many such as biofuel feedstock, human food supplement, medication, and also anti-oxidation activity [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Yields of extraction in UAE are affected by particle sizes, types of solvent, temperature, solvent to biomass ratios, and time of extraction are critical parameters in the UAE method to obtain high yields [14]. Different types have been employed to extraction the protein, include methanol, mixture of methanol and ethanol [5], distilled water [6,10], and sodium phosphate buffer [7]. In this paper, we aimed to study the effect on different solvent types, ratios of solvent to biomass, and extraction time with the UAE of Spp to determine the relatively best condition for protein recovery.…”
Section: Introductionmentioning
confidence: 99%